2023
DOI: 10.1002/aesr.202200204
|View full text |Cite
|
Sign up to set email alerts
|

Toward Rational Design of Ordered Heterostructures for Energy and Environmental Sustainability: A Review

Abstract: Precise synthesis of high‐quality, sophisticated heterostructures by ordered assembly of small nanomaterials is a key step to gain advanced materials that have elaborate functionalities, collective properties, and enhanced stabilities for mitigating the energy and environment crisis. Intricating in the structure, size, and shape of nanomaterials, ordered assembly of isotropic or anisotropic nanoscale building blocks to create specified heterostructures remains challenging, owing to the extraordinary challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 224 publications
0
4
0
Order By: Relevance
“…To generate a colloidal solution of Cu 2 [Fe(CN) 6 ], a water-in-oil microemulsion was formed through the combination of CuSO 4 and K 4 [Fe (CN) 6 ], aided by the surfactant sodium bis(2-ethylhexyl) sulfosuccinate. 43 It was observed that the copper hexacyanoferrate aggregates in the microemulsion solution obeyed Beer's Law and exhibited isotropy. Because of the particle band transition interaction, discernible blue shifts in the UV spectra were observed with an increase in the water to surfactant molar ratio.…”
Section: Template-based Methodsmentioning
confidence: 99%
“…To generate a colloidal solution of Cu 2 [Fe(CN) 6 ], a water-in-oil microemulsion was formed through the combination of CuSO 4 and K 4 [Fe (CN) 6 ], aided by the surfactant sodium bis(2-ethylhexyl) sulfosuccinate. 43 It was observed that the copper hexacyanoferrate aggregates in the microemulsion solution obeyed Beer's Law and exhibited isotropy. Because of the particle band transition interaction, discernible blue shifts in the UV spectra were observed with an increase in the water to surfactant molar ratio.…”
Section: Template-based Methodsmentioning
confidence: 99%
“…In light of the escalating energy crisis and growing environmental concerns, there is an imperative to explore energy storage solutions that are not only environmentally friendly but also boast higher energy density. Lithium–sulfur (Li–S) batteries, with sulfur as the cathode and lithium as the anode, are expected to become the next generation of energy storage devices due to their high theoretical specific capacity (1675 mAh g –1 ), high energy density (2600 Wh kg –1 ), sufficient sulfur reserves, and environmental friendliness. However, the problems of lithium polysulfides’ (LiPSs) shuttle effect, insulating properties of sulfur and lithium sulfide, and lithium dendrites produced by uneven lithium ion deposition have been hindering the practical application of Li–S batteries. …”
Section: Introductionmentioning
confidence: 99%
“…Advanced catalysts can harvest the renewable energy to create alternatives of fossil fuels and transform the development of the modern society. [1] Among them, orderly heterostructured nanomaterials, which integrate nanomaterials of complementary structures and dimensions into single-entity nanostructures, [2] DOI: 10.1002/smll.202302683 have hold great promise for key applications including CO 2 reduction reaction (CRR), [3] hydrogen evolution reaction, [4] N 2 fixation, [5] chemical synthesis, [6] pollutant degradation, [7] etc. Developing a facile tool to prepare ordered heterostructures as advanced catalysts is therefore very appealing yet remains challenging.…”
Section: Introductionmentioning
confidence: 99%